Development of a level A in vitro-in vivo correlation for extended release dosage forms of quetiapine fumarate - Gonçalves de Lima, L.; Rossi de Campos, D. (Drug Research, 2016)
Quetiapine is an atypical antipsychotic recommended as first-line treatment for acute bipolar depression. The extended-release quetiapine formulation is intended to be administered as an once-daily dosing. The development of an in vitro-in vivo correlation (IVIVC) and the use of in vitro data to predict in vivo bioavailability parameters has been of great interest for the rational development and evaluation process for extended release dosage forms. The aim of this study was to develop an IVIVC for quetiapine extended release formulation. In vitro dissolution rate data were obtained using USP apparatus 2 at 50 rpm, in 3 bio-relevant dissolution media with different pH values (1.2, 4.5 and 6.8). The drug release profiles of the 2 extended release dosage forms were compared using the similarity factor (f2). The relative bioavailability of quetiapine was evaluated by a single-dose, randomized-sequence, open-label, 2 period cross over study with 16 healthy volunteers. A linear level A IVIVC model was established using percentage of absorbed and dissolved data obtained at pH 1.2. The developed IVIVC model was employed to predict quetiapine concentration-time profiles, as well as the bioequivalence parameters for test formulation. Percent prediction errors were estimated for Cmax and AUC to evaluate the validity of the correlation. The values did not exceed 15%, proving the predictability of the correlation model. In conclusion, the established level A IVIVC model proved to be an excellent tool for predicting the rate and extent of quetiapine absorption as characterized by Cmax and AUC for test formulation.
Keywords: quetiapine; IVIVC; extended release; dissolution; bioavailability